Generating an SVM Kernel function using genetic algorithm - IMMER, BALDOS (Archīum Ateneo, 2012)
SVMs' performance is affected greatly by the choice of kernel function and kernel parameters. This study made use of a complete binary tree of depth 3 and the Genetic Algorithm to automate the non-trivial task of finding a kernel function that best classi